Enhancing Employee Performance in Sasirangan MSMEs: The Power of Engagement and Motivation - Bustani Bustani; Mohdari Mohdari; Jumangin Jumangin (Journal of Research in Social Science and Humanities, 2025)
This research examines the impact of employee engagement on the performance of employees within Sasirangan MSMEs in Banjarmasin, with motivation serving as a mediating factor. The results reveal that employee engagement influences performance both directly and indirectly through motivation. High levels of engagement foster a positive connection between employees and the organization, which in turn strengthens their dedication and enhances the quality of their work. Motivation, whether intrinsic or extrinsic, plays a critical role as a mediator, amplifying the effect of employee engagement on performance. These findings are consistent with Social Exchange Theory, which posits that mutually beneficial relationships between employees and organizations lead to improved overall outcomes. From a practical perspective, this study highlights the importance of implementing strategies that enhance employee engagement for MSMEs, particularly Sasirangan MSMEs. Initiatives such as recognizing employee contributions, providing opportunities for personal growth, and cultivating a supportive work environment can significantly boost employee motivation, thereby improving performance. By fostering a culture of engagement, MSMEs can increase both the quantity and quality of work, contributing to greater organizational success and long-term sustainability. These insights enhance the theoretical understanding of employee engagement and offer actionable strategies for MSME managers to optimize performance through a motivated and engaged workforce.